The Impact of a Material’s Inherent and Process Stress on Meeting Specification and Tolerances: A Six Sigma Case Study - Jimerson, Brittney; Fahmy, Yusuf; Fender, Joe; Nelms, Linda; Powell, Ted; Yearout, Robert (International Journal of Industrial Engineering: Theory, Applications and Practice, 2009)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> 0 false 18 pt 18 pt 0 0 false false false <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; @page Section1 size:8.5in 11.0in; margin:1.0in 1.25in 1.0in 1.25in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> <!–StartFragment–> This Six-Sigma Case Study was conducted in a local aerospace company that produces high quality precision-machined jet engine components. These complex turbine components have thin walls that must meet tight tolerances. Disks, shafts, rotating seals, plates, and cases range in size from 3" to 80" in diameter. This case focused on a 16” (diameter) rear cooling plate whose production required 18 machining processes. The objective was to determine if it was possible to eliminate the final manual lathing process. Manual lathing was used as the last step because the material characteristics of the plate and the stress induced by the previous processes caused the final product to expand. Stress can cause unsatisfactory changes in the plate’s dimensions. Stress is not only inherent in the material’s internal properties but is also induced during machining. It is critical that the operator’s cut is precise and does not remove too much material. During the two most critical steps of 18, measurements were taken. It was theorized that relaxing the first process tolerances could allow later processes to be numerically machine controlled to conform closer to the prescribed tolerance of the final product. Plates were tested using these revised tolerances. After the plate was shot peened (a stress redistribution process) measurements confirmed that non-conformance had been eliminated and the final machining process could be discontinued. Cost savings for eliminating the last machining and inspection process was 268 per plate or an annual saving of approximately 11% of total cost for the item studied. <!–EndFragment–>